Consistent one-bay frame simplified model for efficient seismic evaluation of steel moment frame buildings with equal and unequal bay lengths. (December 2021) - Hosseini, Mojtaba; Ahmadie Amiri, Hossein; E. Estekanchi, Homayoon
Abstract: A Consistent One-Bay Frame (COBF) simplified model for the efficient estimation of Engineering Demand Parameters (EDPs) in Steel Moment Resisting Frames (SMRFs) with equal and unequal bay lengths is proposed. The geometry of the Substitute One-Bay Frame (SOBF) simplified model has been used, and the elastic and inelastic properties of the beams and columns in this model are determined using an energy consistent approach in a way that the energy balance is established between the members of the original SMRF and the SOBF simplified model. This way, the SOBF simplified model, which originally could only be used for MRFs with equal bay lengths, can now be used for MRFs with any geometric arrangement for bay lengths. Two 9- and 20-story SMRFs with equal bay lengths and two others with unequal bay lengths have been employed as structural models. The concentrated plastic hinges with modified Ibarra-Medina-Krawinkler (IMK) deterioration model have been used to apply strength and stiffness deterioration in numerical models. The accuracy of the proposed simplified model in estimating the EDPs along the height of the structure has been evaluated using Nonlinear Time History Analysis (NLTHA) under 22 pairs of FEMA P-695 earthquake records at the three seismic intensity levels of SLE, DBE, and MCE. The proposed simplified model has been compared with the Consistent Generic (CG) simplified model previously developed for SMRFs. This comparison suggests that the proposed simplified model is more efficient and reliable. Evaluating the seismic performance of the proposed simplified model using the conventional Incremental Dynamic Analysis (IDA) method and the Endurance Time Analysis (ETA) method at all of the seismic intensity levels reveals that using the COBF simplified model along with the ETA simplified method not only reduces the Degrees of Freedom (DOFs) of the original SMRF and the number of the NLTHAs but also leads to a proper estimation of the EDPs of the original SMRF from low seismic intensity level to collapse intensity level. Therefore, it is very helpful to use it for reducing the complexities of the new generation of Performance-Based Earthquake Evaluation.